The Role of Islamic Religious Education and Psychosocial Interventions in Reducing Loss to Follow-Up in HIV Treatment Through Support Group Communication - Evicenna Yuris; Indo Mora Siregar (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Loss to follow up (LTFU) remains a serious challenge in the success of HIV treatment, as it is influenced not only by medical factors but also by psychological, social, and spiritual dimensions. High LTFU rates contribute to antiretroviral therapy (ART) failure, increased morbidity risk, and hindered achievement of HIV control targets. This study aims to analyze the role of Islamic Religious Education and psychosocial interventions in reducing LTFU in HIV treatment through support group communication. The method employed is a literature review of scientific articles, books, and relevant national and international policy documents published over the last ten years. The findings indicate that Islamic Religious Education functions as a spiritual coping mechanism that helps people living with HIV (PLHIV) interpret their illness constructively, strengthen mental resilience, and improve treatment adherence. Its effectiveness is further enhanced when integrated with psychosocial interventions through support groups that reduce stigma, social isolation, and psychological distress. The implications of this study emphasize the importance of integrating religious and psychosocial approaches as a holistic and sustainable strategy to improve retention in HIV treatment.